2018
DOI: 10.1103/physreva.97.013632
|View full text |Cite
|
Sign up to set email alerts
|

Metal-insulator-superconductor transition of spin-3/2 atoms on optical lattices

Abstract: We use a slave-rotor approach within a mean-field theory to study the competition of metallic, Mott-insulating, and superconducting phases of spin-3/2 fermions subjected to a periodic optical lattice potential. In addition to the metallic, the Mott-insulating, and the superconducting phases that are associated with the gauge symmetry breaking of the spinon field, we identify a novel emerging superconducting phase that breaks both roton and spinon field gauge symmetries. This novel superconducting phase emerges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…The energy spectra of excitation modes are determined from the poles of these particle-hole propagators. From equations ( 12) and ( 14), we see that the longitudinal spindensity fluctuation propagator and charge-density fluctuation propagator have the same pole equations as in equation (17). Therefore, the energy spectra of density waves and longitudinal spin waves are indistinguishable under the RPA.…”
Section: Collective Excitation Modesmentioning
confidence: 87%
See 1 more Smart Citation
“…The energy spectra of excitation modes are determined from the poles of these particle-hole propagators. From equations ( 12) and ( 14), we see that the longitudinal spindensity fluctuation propagator and charge-density fluctuation propagator have the same pole equations as in equation (17). Therefore, the energy spectra of density waves and longitudinal spin waves are indistinguishable under the RPA.…”
Section: Collective Excitation Modesmentioning
confidence: 87%
“…The former system usually satisfies the SP(N) or SU(N) symmetries, while the latter can be mapped into more general pseudo-spin models with lower symmetries by precisely controlling interaction parameters, atomic species, and particle numbers. Though enormous research works have been dedicated to exploring exotic quantum phases [10][11][12][13][14][15][16][17] and spin-mixing dynamics [18][19][20][21][22] in the large-spin Fermi gas, normal Fermi-liquid behaviors of such a system are among the most fundamental topics of interest. Based on the Landau Fermi-liquid theory, ground-state properties and lowenergy single-particle excitations of the SP(N) or SU(N) Fermi * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…While most variational approaches are valid only at zero temperature, the mean-field theories are unable to capture quantum fluctuations. However, slave particle theories are valid at both zero and finite temperatures and capable of capturing quantum fluctuations [44][45][46][47][48]. Further, it has been shown that slaveparticle approaches are equivalent to a statistically-consistent Gutzwiller approximation [49].…”
Section: Slave Spin Representation Of the Modelmentioning
confidence: 99%
“…As for spin-3/2, the massive relativistic spin-3/2 quasiparticle has been realized in condensed matter systems [50]. Moreover, it has been reported that superconductivity has been found in spin-3/2 topological semimetals [51][52] and optical lattices [53]. However, quasiparticles with high spin-2 are rarely studied.…”
Section: Introductionmentioning
confidence: 99%